Spatial-Temporal Epidemiology of COVID-19 in Aceh, Indonesia: A Statistical Perspective - Sasmita, Novi Reandy; Phonna, Rahmatil Adha; Kesuma, Zurnila Marli; Kamal, Saiful; Yusya, Nudzran (Unnes Journal of Public Health, 2024)
The development of COVID-19 cases in Aceh for each region based on spatio-temporal is vital information to know. Spatio-temporal mapping is carried out to knowthe distribution of cases in diversity based on regional and time conditions. The timeseries design study was used as the research design in this study. This study aims toobtain factors that influence the incidence of COVID-19 cases in Aceh using paneldata regression analysis and the GTWR model for more accurate results. There arenine variables from 23 districts/cities in Aceh Province in 2020 and 2021. Based onpartial panel data regression analysis, of the eight independent variables that arefactors for analysis, it shows that only the variable number of doctors (p < 0.000),number of Tuberculosis Cases (p < 0.000), Number of Villages with Puskesmas (p< 0.026), and Number of Poor population (p < 0.035) have a significant effect onthe increase in COVID-19 cases in Aceh. The number of Tuberculosis Cases is avery dominant variable. Then, the results of the GTWR analysis using the AdaptiveKernel Exponential weighting function show that regional and time diversity affectthe factors that cause an increase in COVID-19 cases in Aceh. These factors need tobe a concern in controlling COVID-19 cases in Aceh in the future.